Computer Science, asked by mdminhaz, 1 year ago

how can we convert algebraic expressions into QBASIC expressions explain.Give few examples

Answers

Answered by lily31
20
In mathematics, an algebraic expression is an expression built up from integer constants, variables, and the algebraic operations (addition, subtraction, multiplication, division and exponentiation by an exponent that is a rational number).[1] For example, {\displaystyle 3x^{2}-2xy+c} is an algebraic expression. Since taking the square rootis the same as raising to the power {\displaystyle {\tfrac {1}{2}}},

{\displaystyle {\sqrt {\frac {1-x^{2}}{1+x^{2}}}}}

is also an algebraic expression. By contrast, transcendental numbers like πand e are not algebraic.

A rational expression is an expressionthat may be rewritten to a rational fraction by using the properties of the arithmetic operations (commutative properties and associative properties of addition and multiplication, distributive property and rules for the operations on the fractions). In other words, a rational expression is an expression which may be constructed from the variables and the constants by using only the four operations of arithmetic. Thus, {\displaystyle {\frac {3x^{2}-2xy+c}{y^{3}-1}}} is a rational expression, whereas {\displaystyle {\sqrt {\frac {1-x^{2}}{1+x^{2}}}}} is not.

A rational equation is an equation in which two rational fractions (or rational expressions) of the form {\displaystyle {\frac {P(x)}{Q(x)}}} are set equal to each other. These expressions obey the same rules as fractions. The equations can be solved by cross-multiplying. Division by zero is undefined, so that a solution causing formal division by zero is rejected.

Answered by qwwestham
7

Explanation:

Order Symbol Remark

first ( ) Operations within parentheses are performed first.

second ^ Exponentiation is performed before other arithmetic operations.

third *, / Multiplication and division are equal in order of precedence.

forth + , - Addition and subtraction are performed last and are equal in order

of precedence.

Examples

P=(x+y)(x-y)/x2 →P=(X+Y)*(X-Y)/X^2

Y=x2

-2x-4 → Y=X^2-2*X-4

Y=x+r2 + s.r – b →Y=X+r^2/(C*B)+S*R-B

c.b

T=t(1-d).y-t.(1-d)y →T=t*(1-d)*Y-t*(1-d)*Y

A=s.r-y.z+x/5 →A=S*R-Y*Z+X/5

A=s.r-y.z+x →A=(S*R-Y*Z+X)/5

5

A=s+r2

-sr + 7 →A=S+R^2-S*R/S+7

Similar questions